Inter-Religious Court Debates in the Early Tang Dynasty : A Translation of Reports of Nine Public Debates Between Buddhists and Daoists From Daoxuan's Ji gujin Fo Dao lunheng (T 2104) - Assandri, Friederike (Asian Studies E-Books Online, Collection 2026., 2026)
Public debate between representatives of different teachings was an important element in the formation of medieval intellectual culture; but documentation is scarce. Daoxuan's reports are unique as they afford us a vivid glimpse on the debates held at the courts of the early Tang, including philosophical exchanges, jokes, and lively polemics. The reports are part of Buddhist apologetic literature, and thus important documents relating to the introduction and adaptation of Buddhism in China. Their specific nature provides valuable insight into the institution of such debates and their development through interaction of Buddhist and autochthonous forms of intellectual and agonistic debate.